Confining ferric oxides in porous carbon for efficient lithium storage. (1st December 2018) - Wang, Chengzhi; Zhao, Yongjie; Zhai, Ximei; Zhao, Xiuchen; Li, Jingbo; Jin, Haibo
Abstract: With the increasing demand for clean and renewable energy, high-energy and power-density energy storage devices with the environmental and sustainable merits are highly needed. Herein, a convenient and sustainable approach was developed to construct 3D porous multi-component composites. The 3D Fe/Fe3 O4 /carbon composites were successfully derived from daily-used wet wipes. Such composites exhibited superior cycling and rate performance when evaluated as anode materials for lithium ion batteries. A highly reversible capacity of 814.0 mA h g −1 at 180th cycle was delivered at the rate of 0.2 A g −1 . Moreover, a high capacity of 648.1 mA h g −1 was retained after long-life cycling (435 cycles) at the high rate of 1.0 A g −1 . The work provided a prospective guidance for developing eco-friendly, sustainable, high-performance electrode materials for electrochemical energy storage applications.